Legal Protection For Patients Who Are Harmful Due To Medical Actions In The Installation Of Braces Without Medical Records (Study Decision Number 557/PK/PDT/2017) - Justin Ferdy Munthe; Edi Wahjuni; Rhama Wisnu Wardhana (Universitas Islam Darul Ulum, 2024)
Doctors in carrying out medical practice are required to keep medical records which are regulated in the Medical Practice Law. In dentistry, records play a very important role, mistakes made by doctors and dentists by not making medical records are a form of unlawful action. This research aims to examine the form of legal protection for patients if they are harmed due to the actions of a dentist who in practice does not keep medical records and to see how responsible the doctor is for these actions. The method used in this research is normative juridical with a statutory approach, case approach, and conceptual approach. This research discusses forms of legal protection which consist of internal and external forms of legal protection, then discusses the responsibilities of medical personnel based on the absolute prin. The legal protection provided to patients who are harmed by the installation of braces without medical records consists of internal and external legal protection. The principle of absolute responsibility is used basically because of the losses experienced by patients due to the negligence of medical personnel or doctors, which is called negligence in this case as a health service provider, so that Article 60 (2) of the Consumer Protection Law is imposed. In addition, the Judge's Law consideration (ratio decidendi) in Decision Number 557/Pk/Pdt/2017 is clearly very wrong and not based on law because in this case the complainant has attached evidence of disciplinary sanctions.ciple and the principle of error and discusses the legal considerations of judges.